A fungating spica. (21st January 2015) - Chan, Yuen; Selvaratnam, Veenesh; Garg, Neeraj
Abstract : Developmental dysplasia of the hip (DDH) is a common paediatric orthopaedic problem. There are various options for treatment dependent on the age and presentation. In closed and open reduction of DDH, we use a hip spica cast for immobilisation after the procedure. We present an unusual case of fungal growth on a hip spica. A 7-month-old girl presented to our institution with clusters of yellowish-white outgrowths resembling mushrooms from her spica. To the best of our knowledge, this is the first reported case of fungal growth on a hip spica following DDH treatment. It is of utmost importance to be aware of any growth on a hip spica, as this requires a prompt change of spica to avoid further complications. We recommend that the integrity of the spica and the skin be checked at regular intervals in patients with a hip spica.